2022
DOI: 10.1038/s41523-021-00371-0
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab overcomes chemotherapy resistance in mesenchymal stem-like breast cancer by negating autocrine IL-1A induction of IL-6

Abstract: Triple-negative breast cancer (TNBC) patients with mesenchymal stem-like (MSL) subtype have responded poorly to chemotherapy whereas patients with basal-like 1 (BL1) subtype achieved the best clinical response. In order to gain insight into pathways that may contribute to the divergent sensitivity to chemotherapy, we compared the inflammatory profile of the two TNBC subtypes treated with docetaxel. Cellular signaling analysis determined that docetaxel activated MAPK pathway in MSL TNBCs but not BL1 TNBCs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Cytokines and growth factors secreted in cancer cells can lead to persistent activation of STAT3 and, consequently, to tumorigenesis. Among cytokines, based on its association with drug resistance, IL-6 could be a relevant therapeutic target [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and growth factors secreted in cancer cells can lead to persistent activation of STAT3 and, consequently, to tumorigenesis. Among cytokines, based on its association with drug resistance, IL-6 could be a relevant therapeutic target [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pre-clinical data demonstrated that IL6 blockade combined with CD40 stimulation sensitized glioblastoma to immune checkpoint inhibitors and improved survival ( 129 , 130 ). Likewise, pre-clinical investigations revealed that targeting of the IL6 signaling might be beneficial for other cancers as well, where bad prognosis is associated with high IL6 level such as renal cell carcinoma ( 131 , 132 ), non-small cell lung cancer ( 133 ), and breast cancer ( 134 ). We found a single, currently suspended clinical trial of the IL6R antibody tocilizumab for gliomas and glioblastoma treatment (NCT04729959), trials for metastatic breast cancer (NCT03135171), non-small lung cancer among others (NCT04940299, Table 4 ).…”
Section: Molecules Involved In the Ctc Heterotypic Interaction And Kn...mentioning
confidence: 99%
“…Based on this finding, a Phase I clinical trial started from 2017 with combined treatment including trastuzumab and tocilizumab for patients with metastatic trastuzumab-resistant HER2+ breast cancer was carried out (NCT03135171). According to the reported literature, IL-6 signaling is a major determinant of TNBC cell proliferation and viability ( 123 ), and this chemotherapy-associated inflammatory cytokine may promote resistance mechanisms in TNBC cells as well ( 124 ). A Phase Ib/II, open-label, multicenter, randomized umbrella study is being carried out to evaluate the efficacy and safety of multiple immunotherapy-based treatment combinations including tocilizumab in patients with metastatic or inoperable locally advanced TNBC (NCT03424005).…”
Section: Il-6’s Functional Role In Breast Cancer Developmentmentioning
confidence: 99%